21.0k views
1 vote
What is 4(2×-7)+3(3×-1)=3(2-×)​

User Hgminh
by
4.9k points

2 Answers

4 votes

Answer:

x =
(71)/(3)

Explanation:

1. Simplify/distribute each side.


4(2)(-7)+3(3)(-1)=3(2-x)


4(2)(-7)+3(3)(-1)=(3)(2)+(3)(-x)


-56+-9=6+-3x

2. Flip the equation around.


-3x+6=-65

3. Subtract 6 to balance the equation.


-3x+6-6=-65-6


-3x=-71

4. Divide each side by 3. We know they are in the same fact family.


(-3x)/(-3) = (-71)/(3)

User Sebastian Serrano
by
4.7k points
3 votes

Answer:

x=37/20

Explanation:

4(2x-7)+3(3x-1)=3(2-x)

8x-28+9x-3=6-3x

17x+3x=6+31

20x=37

User Scrappy Cocco
by
5.1k points